Evaluating the Efficacy of Combined Surgery for Cataract and Glaucoma: A Comparative Analysis of Visual Acuity, Intraocular Pressure, and Anterior Chamber Depth: Efficacy of Combined Surgery for Cataract and Glaucoma - Munir, Muhammad Sajid; Chaudhary, Mariam Zakia; Arshad, Muhammad; Siddiqui, Sohail Ahmed; Mirza, Umair Tariq; Sharif, Nusrat (Pakistan Journal of Health Sciences, 2024)
Glaucoma is characterized by an abnormal increase in intraocular pressure, leading to optic nerve damage and permanent visual impairment. Cataract is characterized by lens opacity that impairs vision but can be reversed. Objective: To compare pre and post-operative average visual acuity, intraocular pressure, anterior chamber angle, and anterior chamber depth in patients with cataract and narrow angle glaucoma undergoing combined phacoemulsification, intraocular lens implantation, and trabeculectomy. Methods: A quasi-experimental study was carried out at Niazi Welfare Foundation Teaching Hospital Sargodha from June 2022 to December 2023. Total 107 patients with both cataracts and narrow angle glaucoma were included. Post-surgery, average visual acuity, intraocular pressure, anterior chamber angle, and anterior chamber depth were assessed at various postoperative intervals (1 day, 1 week, 1 month, 3 months, and 6 months). The Patient's symptoms improved, with visual acuity and average anterior chamber depth increasing by more than 50% compared to pre-surgery was considered as significant. Data were analyzed by SPSS version 25.0. P-value <0.05 was considered as significant. Results: Results of the study yielded significant improvements in average visual acuity, intraocular pressure (IOP), anterior chamber angle, and anterior chamber depth post-operatively with complication rate of 6.52%. Conclusions: We concluded that combined phacoemulsification with intraocular lens implantation (IOL) and trabeculectomy may be an effective approach for managing intraocular pressure (IOP) and improving visual acuity in patients with narrow angle glaucoma and cataract.